Primary Cutaneous Small Cell Variant of Anaplastic Large Cell Lymphoma: A Case Series and Review of the Literature. (December 2017) - Magro, Cynthia M.; Momtahen, Shabnam; Kiuru, Maija
Abstract : Abstract: Primary cutaneous anaplastic large cell lymphoma (ALCL), similar to systemic ALCL, has as its histomorphologic hallmarks cohesive sheets of large lymphoid cells expressing CD30. Several morphologic variants of systemic ALCL have been reported, including the common (classic) type, lymphohistiocytic, and small cell variants. The small cell variant of ALCL is characterized by a predominant cytomorphology which is unexpected for ALCL, being in the context of a small- to medium-sized hyperchromatic atypical lymphocyte. Although well recognized in its systemic form including cases with secondary cutaneous involvement, it is less well characterized as a form of primary cutaneous ALCL. In this study, we collected 8 cases of primary cutaneous small cell variant of ALCL and examined their clinical, histologic, and phenotypic features. All patients were middle aged to older adult men; the youngest patient was a 46-year-old man with underlying hepatitis C. In one case, there was a history of lymphomatoid papulosis. In all patients, the disease was in the context of a local regional presentation. Patients were treated with complete excision and/or radiation except in one in whom chemotherapy was administered. In all but one patient, the cutaneous presentation was a regionally confined process; however, in 2 cases, recurrent disease occurred, and in 25% of cases, extracutaneous dissemination specifically to regional lymph nodes was observed. Although there was nodal involvement, there was no dissemination to bone marrow or peripheral blood; no patient has died because of disseminated lymphoma. In all cases, there was a predominance of small atypical hyperchromatic cells with a variable background of larger hallmark cells typical of ALCL. Epidermotropism was seen in half of the cases, and in one case, there was striking pseudoepitheliomatous hyperplasia. The smaller cells demonstrated CD30 positivity, and the neoplastic cells showed a CD4-positive phenotype with a variable expression of cytotoxic proteins in about half of the cases, whereas in the remaining cases, a double negative phenotype was observed. Epithelial membrane antigen expression was observed in the cases tested. In our literature review, similar demographics were observed with a comparable percent of cases with extracutaneous dissemination; one case manifested an aggressive clinical course eventuating in death. In summation, the small cell variant of primary cutaneous ALCL exhibits distinctive features clinically and histologically. While exhibiting an overall higher incidence of extracutaneous dissemination, the prognosis fairs better compared with other forms of cutaneous T-cell lymphoma associated with extracutaneous dissemination, an event that defines a harbinger of aggressive disease.